Renewable bio-phenols from in situ and ex situ catalytic pyrolysis of Douglas fir pellet over biobased activated carbons. Issue 4 (20th February 2018) - Yang, Zixu; Lei, Hanwu; Qian, Kezhen; Zhang, Yayun; Villota, Elmar
Abstract : Activated carbon catalyst prepared by phosphoric acid activation of biomass significantly promoted the production of phenolics free of methoxy substitutes. Abstract : In situ and ex situ catalytic upgrading of pyrolysis vapors from Douglas fir pellets in the presence of activated carbon (AC) prepared by chemical activation was studied in a microwave pyrolyzer. The in situ catalytic upgrading configuration gave lower bio-oil yields (10.25–25.5 wt%) than ex situ catalytic upgrading configuration (20.03–32 wt%). The bio-oil yield from the in situ upgrading process was significantly affected by both catalytic reaction temperature and catalyst to biomass ratio. However, the bio-oil yield from ex situ upgrading process was only significantly affected by catalyst to biomass ratio. Bio-oils compositional analysis indicated that the ex situ upgrading process generated higher phenols concentration (4.14–19.76 mg ml −1 ) than in situ upgrading (4.14–9.90 mg ml −1 ). However, the selectivity of phenols from in situ upgrading process reflected by the peak area percentages was higher than that from ex situ upgrading. The catalyst recycling tests showed that the prepared AC catalyst can be reused for three times in phenol-rich bio-oil production via catalytic microwave pyrolysis.